Transient Modelling of Heat Loading of Phase Change Material for Energy Storage - W. M., Asyraf; Vasu, Anusuiah; Hagos, F. Y.; M. M., Noor; R., Mamat (EDP Sciences, 2017)
As the development of solar energy is getting advance from time to time, the solar concentration technology also get the similar attention from the researchers all around the globe. This technology concentrate a large amount of energy into main spot. To collect all the available energy harvest from the solar panel, a thermal energy storage is required to convert the heat energy to one of the purpose such as electrical energy. With the idea of energy storage application that can be narrow down to commercial application such as cooking stove. Using latent heat type energy storage seem to be appropriate with the usage of phase change material (PCM) that can release and absorb heat energy at nearly constant temperature by changing its state. Sodium nitrate (NaNO3) and potassium nitrate (KNO3) was selected to use as PCM in this project. This project focus on the heat loading process and the melting process of the PCM in the energy storage using a computer simulation. The model of the energy storage was create as solid three dimensional modelling using computer aided software and the geometry size of it depend on how much it can apply to boil 1kg of water in cooking application. The material of the tank will use a standard stainless steel and pure copper as heat exchanger tube. With the XCELTHERM MK1 as the heat transfer fluid flow through the PCM medium in the tank, an analysis was performed using ANSYS FLUENT simulation software in a transient state. The simulation run on different value of velocity but kept controlled under laminar state only, then the relationship of velocity and heat distribution was studied. The melting process of the PCM also has been analyzed in this project.